José Ángel Valente and Antonio Colinas’ Literary Essays: Characteristics of a Genre - Badía Fumaz, Rocío (Madrygal. Revista de Estudios Gallegos, 2015)
Based on the literary essays by José Ángel Valente (Las palabras de la tribu, La experiencia abisal or La piedra y el centro) and Antonio Colinas (El sentido primero de la palabra poética, Sobre la Vida Nueva or Del pensamiento inspirado), this paper aims to describe the poetics written by these poets through their primary and secondary features.
Keywords: Poetics; autopoetics; literary essay; José Ángel Valente; Antonio Colinas